1990
DOI: 10.1152/jappl.1990.69.6.2034
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lung mechanics and reactivity with age after viral bronchiolitis in beagle puppies

Abstract: We measured changes with growth in lung function and airway reactivity after acute canine parainfluenza virus type 2 (CPI2, n = 5), canine adenovirus type 2 (CAV2, n = 7), and sequential CAV2-CPI2 (n = 6) infections or no infection (controls, n = 6) in beagle puppies (age approximately 79 days). In the CPI2 and CAV2 groups, a lower respiratory illness developed by day 3 postinfection with clinical recovery by day 14. In the CAV2-CPI2 group, puppies were inoculated initially with CAV2 and 12 days later with CPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…This observation is consistent with our previous study indicating that effects on subsequent lung growth are the same in CAV2-CP12 puppies as in CP12 or CAVZ infected puppies alone. 25 We have recently demonstrated that over a period of approximately 239 days, airway res nsiveness to histamine gradually increased with age.2qowever, we do not believe that the increased histamine responsiveness noted in the CAV2-CP12 group can be explained by our previous observation. First, the disparity in age at the time of CP12 infection in the CAV2-CP12 and CP12 groups was only 14 days which is too short a time to distinguish any age related differences in airway responsiveness.…”
Section: :Ial Viral Respiratory Infection In Beagle Puppies 241mentioning
confidence: 60%
“…This observation is consistent with our previous study indicating that effects on subsequent lung growth are the same in CAV2-CP12 puppies as in CP12 or CAVZ infected puppies alone. 25 We have recently demonstrated that over a period of approximately 239 days, airway res nsiveness to histamine gradually increased with age.2qowever, we do not believe that the increased histamine responsiveness noted in the CAV2-CP12 group can be explained by our previous observation. First, the disparity in age at the time of CP12 infection in the CAV2-CP12 and CP12 groups was only 14 days which is too short a time to distinguish any age related differences in airway responsiveness.…”
Section: :Ial Viral Respiratory Infection In Beagle Puppies 241mentioning
confidence: 60%
“…To date, several etiologies have also implicated in the pathogenesis of animal BOOP. Experimentally infected dogs with adenovirus [42][43][44], Mycoplasma [45], or cattle clinical infected bovine respiratory syncytial virus pneumonia occasionally develop BOOP [46]. Accidental intra-airway exposure of dog with a noninfectious agent oleic acid also induced BOOP [47].…”
Section: Discussionmentioning
confidence: 99%
“…Quan et al (1990) showed a decrease in lung resistance in the first year of life, while dynamic compliance, static compliance, and specific conductance all increased with age. Robinson and Gillespie (1973) did not show any evidence for a change in lung compliance between dogs aged less than 500 days and dogs aged more than 3000 days, although their data were highly variable.…”
Section: Dogsmentioning
confidence: 96%
“…Data on the changes in lung volume with age in dogs are entirely from in vivo studies (Mauderly, 1974;Robinson and Gillespie, 1973;Quan et al, 1990). All of these studies describe an increase in lung volume with age.…”
Section: Dogsmentioning
confidence: 99%
See 1 more Smart Citation